Current issues of ensuring the planning of operational and service activities of the State Border Guard Service of Ukraine - Bratko, Artem; Datskov , Anton; Bereziuk , Viktor (Social Development and Security, 2021)
In the article the authors analyzed and provided recommendations on the processes of planning operational and service activities of the State Border Guard Service of Ukraine. Conceptual and strategic documents of the state define changes in the use of border guards in modern conditions. Existing forms of operational and service activities acquire a new meaning. The State Border Guard Service of Ukraine, as a law enforcement body of special purpose, is entrusted with new tasks to protect the state border. In this regard, the management system of the State Border Guard Service of Ukraine is undergoing significant changes. The range of tasks of the reserves of the State Border Guard Service of Ukraine is expanding. Effective, mobile, equipped with modern weapons, military and special equipment border special forces are being created, which will ensure timely response to military threats to Ukraine’s border security, rationally using the available potential (capabilities). There is an urgent need for compatibility of the planning system with the system adopted in the Armed Forces of Ukraine and NATO on the basis of capabilities. The introduction of operational-service planning activities in the activities of the State Border Guard Service of Ukraine will significantly improve the quality of planning, increase the ability of the State Border Guard Service of Ukraine to perform tasks in the field of state border security. The implementation of these measures, together with other components of the security and defense sector, will ensure Ukraine’s active participation in the implementation of the EU Common Security and Defense Policy and cooperation with NATO to ensure compliance with the requirements for full membership in the North Atlantic Alliance.